Investigating the Status of Distributed Leadership in Senior High Schools in the City of Sanandaj - Khalil Gholami; Younes Sahranavard Nshtifani; Nematollah Azizi (Allameh Tabataba'i University Press, 2014)
The aim of this study was to investigate the status of DL in senior high  schools in Sanandaj and the extent to which DL components are believed by the teachers to be present in the principals' behaviors. The quantitative approach was used in this study. Statistical population consisted of all teachers (male and female) in public  senior  high  schools  in  Sanandaj.  A  sample  of  377  teachers  from  31 schools was selected through the access sampling method and a researcher-made questionnaire  with  Cronbach`s  Alpha  0.95  was  used  for  collecting  the  data. Moreover,  this  questionnaire  demonstrated  four  major  components  such  as Teachers  Professional  development  &  School  improvement,  Traits  of Leadership Team, Democracy  and Comprehensive Support  after the exploratory factor  analysis.  Results  of  the  chi  square  test  showed  that  teachers  generally believe that principals'''' DL is at an average level. Also, the results of the T-test indicated that female teachers believe their principals utilized more DL related behaviors in their profession area than  the male teachers. Finally, based on the results of Aanova, variables of experience and educational level had no impact on  the  teachers''''  evaluation  of  their  principals''''  DL,  that  is  they  reported  the principals DL at the same level.